Traditional Chinese Medicine and COVID-19: Experiences, Lessons, and Suggestions - Zuo-Biao Yuan; Paul S. Amieux (Wolters Kluwer Health/LWW, 2022)
Coronavirus disease-2019 (COVID-19) has now entered its third year as a worldwide pandemic. Unlike the Unites States, over 90% of patients have used traditional Chinese medicine (TCM) in China combined with conventional western medicine. The present minireview/commentary summarizes the experiences of TCM in the treatment of COVID-19 combined with conventional western medicine, lessons from the United States and some additional insights. COVID-19 falls into the category of "dampness−toxin plague" and is divided into five stages: mild stage, moderate stage, severe stage, critical stage, and recovery stage. Clinical trials conducted in China have suggested that TCM treatment plays a significant role in alleviating clinical symptoms, decreasing the time of hospitalization, reducing the overall fatality rate, and providing other beneficial outcomes when combined with conventional western medicine. To date, TCM is not widely used in the American hospital system. Only one TCM clinical trial to treat mild to moderate COVID-19 has been registered with ClinicalTrials.gov. A suggestion of dialogues among associated parties is proposed. TCM has been used as part of an integrative medicine treatment paradigm combined with conventional western medicine for COVID-19 in China. As registered clinical trials combining conventional western medicine with TCM continue to be produced and show positive benefits, the possibilities for TCM integration into treatment protocols for COVID-19 will become more of a possibility in the United States.